CULTURAL CONSTRUCTION IN AMERICAN WOMAN’S IDENTITY IN DARREN STAR’S SERIES, EMILY IN PARIS; A CROSS CULTURAL ANALYSIS - Harefa, Devarianda Setya Helbenna (LINGUA LITERA : journal of english linguistics and literature, 2023)
Abstract Cultural construction is a process of forming a person's identity due to cultural differences. In this study, the writer formulates two problems of study, how Emily as American woman responses to French culture and the impact of cultural construction on Emily’s identity in the series Emily In Paris. This research was analyzed using Chris Barker's cultural studies approach and used the description method to analyze the data. Two concepts applied in this research are subjectivity and identity. These two concepts are also divided into three classifications, the first and second classification, showing Emily's way as an American Woman in responding to French culture. Meanwhile, the third classification shows that identity requires recognition from other people.